ANALISIS FRAMING BERITA PEMILIHAN RAYA MAHASISWA DI UIN RADEN FATAH PALEMBANG TAHUN 2023: Studi Kasus Pemberitaan Kericuhan Pada Saat Debat Capresma dan Cawapresma - Anna Nursalamah; Reni; Rizma Yulistiana; Musdalipah; Ramadoni, Muhamad Afdoli (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2024)
The Student General Election at the Raden Fatah State Islamic University of Palembang is one of the campus democracy events that not only functions as a means of electing student leaders, but also as a medium to increase active student participation in political activities. Commonly used social media platforms such as Instagram, WhatsApp, and Facebook play a very important role in shaping student perceptions of candidates and the overall election process. By using framing theory, this study focuses on how the media frames news related to the Student General Election and its impact on students' political decisions. This study aims to analyze how the framing of news about the student general election at UIN Raden Fatah Palembang influences students' political decisions. By using qualitative methods and a questionnaire of 11 questions, this study found that most students were influenced by the news they received. The results of the data management that has been carried out can be concluded that most students are influenced and some students are not influenced by the news they get either through social media or the special platform of UIN Raden Fatah Palembang. The research findings show that news framing has a significant impact on students' political decisions.